Hyaline Vascular Castleman’s Disease: A Case Report - Ender İnci; Aydın Mamak; Levent Dereköylü; M. Güven Güvenç; Harun Cansız; Hilal Akı (Turkish Archives of Otorhinolaryngology, 2003)

(untitled)
Castleman’s disease is a rare lymphoproliferative disorder that has a benign character and has no etiological factor. Three histological types have been described; hyaline vascular, plasma cell and mixed type. Usually it seems lymph node hyperplasia in mediastinum and rare solitary involvement of the neck. In hyaline vascular type total resection of the mass cure the disease but in multicentric type mortality rate is high. We report a 36-year-old woman with non-fixated solitary mass located in left cervical region. After total resection of the mass, made histological research and found hyaline vascular type Castleman’s disease. There are no complication or recurrence of the disease after one-year observation.